2010
DOI: 10.2134/agronj2010.0166
|View full text |Cite
|
Sign up to set email alerts
|

Apparent Nitrogen Recovery from Fall‐Applied Ammoniated Phosphates and Ammonium Sulfate Fertilizers

Abstract: Phosphorus fertilizer is frequently fall-applied for corn (Zea mays L.). Diammonium-(DAP) or monoammonium-phosphates (MAP) are the preferred P fertilizers and the N in MAP and DAP is assumed to be available for corn. Our objective was to evaluate the eff ect of application time on availability of ammoniated-phosphate N to the crop in two diff erent environments. In a laboratory study, MAP and DAP at rates of 70 and 140 mg N kg −1 soil were incubated at either 80 or 120% fi eld capacity (FC). Nitrifi cation pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
1

Year Published

2012
2012
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(15 citation statements)
references
References 20 publications
1
13
1
Order By: Relevance
“…The consensus among studies was that a yield response of corn or soybean was observed when STP values were very low to low (9-16 mg kg −1 ) and a yield increase to deep placement of P was seldom observed, with a few exceptions [22,24,25,33]. Phosphorus fertilizer application timing and source studies in Illinois have investigated diammonium-phosphate (DAP) or monoammonium-phosphate (MAP) sources and the interaction with application timing (fall or spring) [34]. Spring applications of P resulted in a greater yield response for corn (0.37 to 0.71 Mg ha −1 ) than fall applications [34].…”
Section: Rs Of Phosphorus Managementmentioning
confidence: 99%
See 2 more Smart Citations
“…The consensus among studies was that a yield response of corn or soybean was observed when STP values were very low to low (9-16 mg kg −1 ) and a yield increase to deep placement of P was seldom observed, with a few exceptions [22,24,25,33]. Phosphorus fertilizer application timing and source studies in Illinois have investigated diammonium-phosphate (DAP) or monoammonium-phosphate (MAP) sources and the interaction with application timing (fall or spring) [34]. Spring applications of P resulted in a greater yield response for corn (0.37 to 0.71 Mg ha −1 ) than fall applications [34].…”
Section: Rs Of Phosphorus Managementmentioning
confidence: 99%
“…Phosphorus fertilizer application timing and source studies in Illinois have investigated diammonium-phosphate (DAP) or monoammonium-phosphate (MAP) sources and the interaction with application timing (fall or spring) [34]. Spring applications of P resulted in a greater yield response for corn (0.37 to 0.71 Mg ha −1 ) than fall applications [34]. In Iowa, P application for no-till corn and soybean was evaluated at 20 sites in three years for a fall and spring broadcast application of triple superphosphate (TSP) on soils with STP values ranging between 6 to 29 mg P kg −1 [35].…”
Section: Rs Of Phosphorus Managementmentioning
confidence: 99%
See 1 more Smart Citation
“…To overcome this, unrealistically high rates of ammonium phosphate fertilizers are sometimes used in studies. For example, Fernández et al (2010) applied MAP at an order of magnitude greater than typical rates to quantify soil recovery of N of up to 90 kg N ha −1 , equivalent to 172 kg P ha −1 . Yang et al (2023) applied magnesium ammonium phosphate (i.e., struvite) on an N basis in order to compare N losses relative to urea, of up to 150 kg N ha −1 , equivalent to 360 kg P ha −1 .…”
Section: Resolving the Blind Spotmentioning
confidence: 99%
“…For example, the USDA classifies ammonium phosphate fertilizers as a P fertilizer, and thus N from MAP, DAP, and APP is not included in national fertilizer N budgets (Decock, 2014). In the U.S. Corn Belt, a proportion or in some cases all of the ammonium phosphate N is often excluded from agronomic N budgets (e.g., McGrath, 2022; Nafziger, 2018) based on assumptions or limited evidence that there is variable (i.e., weather‐dependent) availability of ammonium phosphate N to the crop (Fernández et al., 2010). As a result, the magnitude and fate of N co‐applied with P of ammonium phosphates are overlooked, constituting an appreciable blind spot in the anthropogenic N cycle.…”
Section: Overview: Overlooking the N In Ammonium Phosphate Fertilizersmentioning
confidence: 99%